2022
DOI: 10.1021/acs.jmedchem.2c00649
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the RNA G-Quadruplex and Protein Interactome for Antiviral Therapy

Abstract: In recent years, G-quadruplexes (G4s), types of noncanonical four-stranded nucleic acid structures, have been identified in many viruses that threaten human health, such as HIV and Epstein–Barr virus. In this context, G4 ligands were designed to target the G4 structures, among which some have shown promising antiviral effects. In this Perspective, we first summarize the diversified roles of RNA G4s in different viruses. Next, we introduce small-molecule ligands developed as G4 modulators and highlight their ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 227 publications
(468 reference statements)
0
9
0
Order By: Relevance
“…46 Nonetheless, since the discovery of biologically relevant G4s in the eukaryotic chromosomal telomeric DNA consisting of the repeated sequence TTAGGG, 47 an unprece-discovery of telomeres and telomerase. 49,50 So far, a lot of structural information about DNA G4s has been reported which shows a great conformational diversity of G4s, which are recognized as potential drug targets against many human diseases, [51][52][53][54][55][56] particularly cancers. [57][58][59][60][61][62][63][64][65][66][67] The relationship between the sequence, structure and stability of G4s, their interactions with small molecules in vitro and in vivo, and insights into the rational design of G4-selective binding ligands have been well documented and intensively reviewed over the decade.…”
Section: Introductionmentioning
confidence: 99%
“…46 Nonetheless, since the discovery of biologically relevant G4s in the eukaryotic chromosomal telomeric DNA consisting of the repeated sequence TTAGGG, 47 an unprece-discovery of telomeres and telomerase. 49,50 So far, a lot of structural information about DNA G4s has been reported which shows a great conformational diversity of G4s, which are recognized as potential drug targets against many human diseases, [51][52][53][54][55][56] particularly cancers. [57][58][59][60][61][62][63][64][65][66][67] The relationship between the sequence, structure and stability of G4s, their interactions with small molecules in vitro and in vivo, and insights into the rational design of G4-selective binding ligands have been well documented and intensively reviewed over the decade.…”
Section: Introductionmentioning
confidence: 99%
“…The PhenDC3 and TMPyP4 (G4 ligands) were found to slow down the replication fork and disrupt the DNA replication of Kaposi sarcoma-associated herpesvirus . The G4’s structure was also identified in the COVID-19 genome and could be an essential drug target for the inhibition of this virus. , …”
Section: Introductionmentioning
confidence: 99%
“…25 The G4's structure was also identified in the COVID-19 genome and could be an essential drug target for the inhibition of this virus. 26,27 Current studies on G4s have mainly been carried out under diluted solution conditions. However, in reality, the cellular milieu is highly crowded, with a diverse range of molecules, including proteins, polysaccharides, nucleic acids, and other soluble or insoluble substances, occupying a limited amount of available space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] Among them, the roles of viral G4s have been widely investigated and the emerging evidence indicated that G4s involved in regulating viral replication, transcription, assembly, virulence, etc ., even G4s can co‐evolve with virus. [ 35 , 36 ] In addition, several G4 ligands have shown potentially interesting antiviral activity in various viruses, including Hepatitis C virus (HCV), [ 37 ] the Zika virus (ZIKV), [ 38 , 39 ] the Ebola virus (EBOV) [ 40 ] and SARS‐CoV‐2.…”
Section: Introductionmentioning
confidence: 99%